New forms of regional interaction between universities and industry evidence from Germany - Knut Koschatzky (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2014)
More recently, the contribution of German universities to regional knowledge and technology transfer and their third role is particularly pronounced by the fact that the range of their tasks as well as their autonomy has increased significantly. Terms like new public management, self-control and strategic management underline this new role. Based on a stronger regional focus in national innovation policy, the objective of the paper is to analyze the recent developments of universities with regard to their regional activities. Of special interest will be the identification of the most prominent forms of the third role of universities and the analysis of new organizational modes of collaboration and interaction with industry. Based on a survey among German professors and the management levels of universities and by introducing the 'Research Campus' (Forschungscampus) program recently implemented by the German government, the paper shows that multilateral, multi-functional networks and long-term institutionalized partnerships are increasingly established.
urn:nbn:de:0011-n-2868986
Keywords: 330